Pelatihan Pengelolaan Keuangan dan Pemasaran Untuk Pengembangan Usaha Warung di Kembangan Utara Jakarta Barat - Lusia Sri Arini; Harnovinsah Harnovinsah; Swarmilah Hariani (LPMP Imperium, 2020)
Community service has been carried out by analyzing the situation of partners who do not get used to doing financial bookkeeping, how to serve food is still not arranged to attract consumers, the cooking area and guest room are not neat and less clean, also how to offer food to consumers that are still not friendly. For this reason, service partners are provided with food stalls by helping them to develop their food stalls. The activities carried out are providing knowledge about bookkeeping, financial management with theory and practice, marketing management, and entrepreneurship. Dining and dining room settings kitchen so that it looks clean and organized. The output of this service is so that the shop owner is more skilled in managing the rice shop business and it is hoped that knowing the above knowledge will be more developed and become the goal of consumers to eat at the rice shop. After training partners get financial knowledge, partners can do bookkeeping every day so that they can design their business development. Marketing and entrepreneurship knowledge can support the success of current and future rice food stalls and in the end, the development of rice stalls will improve the partners' lives and economies. Keywords: Finance, marketing, entrepreneurship